Diet and pancreatic cancer prevention - Casari, I.; Falasca, Marco (MDPI AG, 2015)
Pancreatic cancer is without any doubt the malignancy with the poorest prognosis and the lowest survival rate. This highly aggressive disease is rarely diagnosed at an early stage and difficult to treat due to its resistance to radiotherapy and chemotherapy. Therefore, there is an urgent need to clarify the causes responsible for pancreatic cancer and to identify preventive strategies to reduce its incidence in the population. Some circumstances, such as smoking habits, being overweight and diabetes, have been identified as potentially predisposing factors to pancreatic cancer, suggesting that diet might play a role. A diet low in fat and sugars, together with a healthy lifestyle, regular exercise, weight reduction and not smoking, may contribute to prevent pancreatic cancer and many other cancer types. In addition, increasing evidence suggests that some food may have chemo preventive properties. Indeed, a high dietary intake of fresh fruit and vegetables has been shown to reduce the risk of developing pancreatic cancer, and recent epidemiological studies have associated nut consumption with a protective effect against it. Therefore, diet could have an impact on the development of pancreatic cancer and further investigations are needed to assess the potential chemo preventive role of specific foods against this disease. This review summarizes the key evidence for the role of dietary habits and their effect on pancreatic cancer and focuses on possible mechanisms for the association between diet and risk of pancreatic cancer.